2018
DOI: 10.1007/s11356-018-3769-1
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the effect of indoor air pollution on pneumonia in children under 5 in low- and middle-income countries: a systematic review of evidence

Abstract: Exposure to indoor air pollution increases the risk of pneumonia in children, accounting for about a million deaths globally. This study investigates the individual effect of solid fuel, carbon monoxide (CO), black carbon (BC) and particulate matter (PM) 2.5 on pneumonia in children under 5 in low- and middle-income countries. A systematic review was conducted to identify peer-reviewed and grey full-text documents without restrictions to study design, language or year of publication usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 56 publications
5
38
0
1
Order By: Relevance
“…Higher odds of pneumonia were observed in under-five children whose family uses wood as a source of fuel. This result was in line with studies conducted in India (52), and Sri Lanka (53); and with systematic reviews conducted in Low and Middle income countries (54), and Africa, China and Latin America (55). It was also consistent with a global review conducted by Jackson et al (56).…”
Section: Non-exclusive Breast Feedingsupporting
confidence: 91%
“…Higher odds of pneumonia were observed in under-five children whose family uses wood as a source of fuel. This result was in line with studies conducted in India (52), and Sri Lanka (53); and with systematic reviews conducted in Low and Middle income countries (54), and Africa, China and Latin America (55). It was also consistent with a global review conducted by Jackson et al (56).…”
Section: Non-exclusive Breast Feedingsupporting
confidence: 91%
“…Higher odds of pneumonia were observed in under-ve children whose family uses wood as a source of fuel. This result was in line with studies conducted in India (52), and Sri Lanka (53); and with systematic reviews conducted in Low and Middle income countries (54), and Africa, China and Latin America (55). It was also consistent with a global review conducted by Jackson et al (56).…”
Section: Non-exclusive Breast Feedingsupporting
confidence: 91%
“…Previous studies have measured single pollutants or used proxies measurements in the absence of observed primary data (Broor et al, 2001;Mahalanabis et al, 2002;Dherani et al, 2008;Bassani et al, 2010;Dhimal et al, 2010;Dionisio et al, 2012;Bruce et al, 2013;Jackson et al, 2013;Karki et al, 2014;Ram et al, 2014;Shibata et al, 2014;Zar & Ferkol, 2014;Buchner & Rehfuess, 2015;Kelly et al, 2015;Sonego et al, 2015;Howie et al, 2016;PrayGod et al, 2016;Mortimer et al, 2017a). We have previously reported that when directly measuring pollutants, there was no association with pneumonia incidence, but when using biomass fuel as a proxy, there was (Adaji EE et al, 2019). This highlights the need for targeted approaches for measuring indoor pollutant levels.…”
Section: Discussionmentioning
confidence: 79%